2013
DOI: 10.1080/0972060x.2013.794045
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents from Leaves of EndemicScutellaria havanensisJacq. in Cuba

Abstract: The volatile constituents from leaves of endemic Scutellaria havanensis Jacq. in Cuba was studied by hydrodestillation and GC-MS. Twenty-five compounds were identified, of which the most prominent were β-caryophyllene (75.6 %), α-humulene (11.6 %) and Caryophyllene oxide (2.6 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The overall FA profile obtained in the present work was in full agreement with those reported earlier for seed oils of Salvia species . On the other hand, there was a qualitative uniformity in the distribution of FAs among the examined Salvia species.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The overall FA profile obtained in the present work was in full agreement with those reported earlier for seed oils of Salvia species . On the other hand, there was a qualitative uniformity in the distribution of FAs among the examined Salvia species.…”
Section: Resultssupporting
confidence: 92%
“…While ω ‐6 and ω ‐3 FAs are very important for pharmaceutical and cosmetic industries, Salvia seeds may be considered as potential sources of these special FAs. According to our results, the amounts of UFAs were high in Salvia seed oils and were comparable with those reported in Stachys , Vitis , Origanum , Echium , and other Salvia species . The presence of the two dietary essential FAs ALA and LA at high amounts in Salvia seed oils makes their nutritional and pharmaceutical values superior to many industrial oil seeds.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Healthcare and culinary usage are now becoming increasingly prevalent as compared to synthetic pharmaceutical goods to safeguard the natural balance due to their bactericidal and fungicidal capabilities. Extraction by steam distillation or expression, for instance, is favored in certain circumstances [55][56][57][58][59][60]. Extraction with lipid-soluble solvents and, in some cases, supercritical carbon dioxide is preferred for fragrance applications.…”
Section: Essential Oilsmentioning
confidence: 99%
“…Phytochemical screening of extracts from aerial parts of S. havanensis reported the presence of flavonoids, coumarins, triterpenoids, steroids, alkaloids, free amine groups, sugars, quinones, resins, and saponins [21]. In addition, twenty-five volatile compounds from the extract of aerial parts of S. havanensis were identified, β-caryophyllene (75.6%) being the most prominent compound [21]. Studies on Scutellaria extracts have shown its role in oxidative stress associated with several human pathogeneses [22][23][24].…”
Section: Introductionmentioning
confidence: 99%